Technology in the educational processes of basic education in Peru - Vega Infantas, Maribel Liliana (2023)
This research project aimed to give a perspective on the implementation of technologies in basic education in Peru. How the automation of basic education processes in Peru helps students, parents, teachers, and administrative staff to reduce time, to have better educational quality, and to obtain indicators for the teacher and student. The methodology of the research is a sequence of activities that allow us to design a framework for process technologies in basic education in Peru. Based on online surveys, it was possible to obtain information from people who want a change in the processes of education, such as: having more reach to information with the help of the internet for which mobile applications or web applications are needed, the delivery of evaluations and enrolment via online, taking advantage of technology for the benefit of the student and teachers, and other processes. The research has a qualitative approach. It is also descriptive in scope with the help of other studies or tests conducted. For the creation of this article, we used surveys, scientific journals, and our own experience as practitioners. If we want to improve education, it is necessary to improve educational processes with the help of technology and the internet.